2013
DOI: 10.1016/j.ecoleng.2013.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Extreme inefficiency of two conventional, technical fishways used by European river lamprey (Lampetra fluviatilis)

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
72
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 52 publications
3
72
0
Order By: Relevance
“…The ability of P. fluviatilis to utilize fish passage structures on blockages in European rivers was shown 260 by Aronsuu et al (2015), who revealed that all individuals that used a natural-like fish-way (fish pass) were successful in passing the barrier, with individuals showing a strong preference to using this over a technical fish-way. Other studies have revealed technical fish-265 ways are also problematic for P. fluviatilis to utilize (Laine et al, 1998;Q4 Lucas et al, 2009;Foulds and Lucas, 2013), with Aronsuu et al (2015) suggesting that natural-like fish ramps might be a good solution to enhance their passage over low-head barriers. Nevertheless, 270 Lasne et al (2015) revealed that barrier removal can be the most effective mechanism to enable P. marinus passage, with higher numbers of nests that were more consistently distributed occurring several years after barrier removal in a French coastal stream.…”
Section: Physical Obstructionsmentioning
confidence: 99%
See 4 more Smart Citations
“…The ability of P. fluviatilis to utilize fish passage structures on blockages in European rivers was shown 260 by Aronsuu et al (2015), who revealed that all individuals that used a natural-like fish-way (fish pass) were successful in passing the barrier, with individuals showing a strong preference to using this over a technical fish-way. Other studies have revealed technical fish-265 ways are also problematic for P. fluviatilis to utilize (Laine et al, 1998;Q4 Lucas et al, 2009;Foulds and Lucas, 2013), with Aronsuu et al (2015) suggesting that natural-like fish ramps might be a good solution to enhance their passage over low-head barriers. Nevertheless, 270 Lasne et al (2015) revealed that barrier removal can be the most effective mechanism to enable P. marinus passage, with higher numbers of nests that were more consistently distributed occurring several years after barrier removal in a French coastal stream.…”
Section: Physical Obstructionsmentioning
confidence: 99%
“…Elevated water flow increases their migratory activity (Masters et al, 2006) and this assists their passage through barriers that otherwise can be impassable at reduced flows (Lucas et al, 2009;Foulds and Lucas, 2013). Where flows are exces-245 sive, however, movements of both species might be hindered by their elongated body morphology and lack of paired fins that reduces their ability of negotiating highvelocity flows when compared to most other migratory fishes (Keefer et al, 2013;Foulds and Lucas, 2013). They 250 demonstrate typical anguilliform swimming under these velocities, referred to as a "burst-and-attach" pattern (Adams and Reinhardt, 2008), which is generally ineffective in high velocity areas such as weir orifices or salmonid fish passes, as these often lack suitable attachment 255 surfaces and/or the water velocity exceeds their critical swimming speeds (Adams and Reinhardt, 2008;Foulds and Lucas, 2013).…”
Section: Physical Obstructionsmentioning
confidence: 99%
See 3 more Smart Citations